2021
DOI: 10.5430/wjel.v12n1p1
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Effectiveness of Blackboard Learning Management System in Teaching English in the Era of COVID-19

Abstract: The study carries out a detailed review of the overall impact of deploying the Blackboard online platform in the EFL teaching-learning process. In pursuing this aim, this study has followed the narrative literature approach, using analytical and comparative techniques as primary research methods. Numerous studies have been analysed thoroughly to conclude whether these technology-oriented tools directly affect the EFL teaching-learning process. The study also provides a definitive opinion regarding the usefulne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 73 publications
0
22
0
Order By: Relevance
“…Improving teachers' quality of instruction via teacher PD programs has been a top priority in many nations. Since its inception, PD has undergone several changes (Al-khresheh, 2021b;Elliott, 2017;Yates, 2007). Furthermore, according to Hiebert (1999), studies on teacher learning point out that compelling chances to learn new-fangled teaching methods have numerous essential features, such as: "(a) ongoing collaboration of teachers for purposes of planning, with (b) the explicit goal of improving students' achievement of clear learning goals, (c) anchored by attention to students' thinking, the curriculum, and pedagogy, with (d) access to alternative ideas and methods and opportunities to observe" them in action, enabling reflections on the causes for their effectiveness (p.15).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Improving teachers' quality of instruction via teacher PD programs has been a top priority in many nations. Since its inception, PD has undergone several changes (Al-khresheh, 2021b;Elliott, 2017;Yates, 2007). Furthermore, according to Hiebert (1999), studies on teacher learning point out that compelling chances to learn new-fangled teaching methods have numerous essential features, such as: "(a) ongoing collaboration of teachers for purposes of planning, with (b) the explicit goal of improving students' achievement of clear learning goals, (c) anchored by attention to students' thinking, the curriculum, and pedagogy, with (d) access to alternative ideas and methods and opportunities to observe" them in action, enabling reflections on the causes for their effectiveness (p.15).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In a study on faculty members’ perceptions of BB at three different Universities in KSA, El Zawaidi (2014) found that most faculty members considered BB to be easy to use which could assist them in teaching due to its technological features. However, along with reporting the high percentage of positive experiences with BB, Al-Khresheh (2021) also mentioned several issues that could slow down the adoption of this tool. Such issues, as argued by AbuSa’aleek and Shariq (2021) , can include students’ preference issues, technical issues, and timing issues, among others.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Accordingly, a great deal of communication and learning-related tasks (e.g., report and assignment submission, announcements, and information dissemination, etc.) can be accomplished using BB ( Al-Khresheh, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Mohammad Hamad Al-khresheh carried out a detailed review of the overall impact of deploying the Blackboard online platform in the EFL teaching-learning process. The researcher also concludes that teachers need training, encouragement and support to use online teaching tools [6].…”
Section: Introductionmentioning
confidence: 99%